Copper adsorption on calcium alginate beads: equilibrium pH-related models - Veglio', F; Esposito, A; Reverberi, A.P (Hydrometallurgy, 2002)
In the present work, a study of adsorption of copper(II) ions onto calcium alginate beads has been carried out. In spite of many works reported in the literature on this subject (here reviewed), this work was mainly aimed at developing a methodological approach to study adsorption and biosorption of heavy metals considering a mathematical modelling including pH. Generally, in the adsorption isotherms, this parameter must be maintained constant to use the usual equilibrium models, such as Langmuir, Frendlich and Redlich–Peterson equations. pH-edge tests are been proposed and carried out to study the equilibrium and several empirical and semiempirical models are proposed to describe and to fit all the experimental data, including pH as independent variable. pH and equilibrium concentration can be considered at the same time in the mathematical modelling of biosorption equilibrium. A statistical and physical discrimination among rival models has also been performed to select the best model. The results show that pH-edge tests can be used to describe the equilibrium data and that the proposed models are able to fit the experimental results using a mathematical model with just three adjustable parameters. The behaviour of calcium alginate with respect to copper biosorption is characterised over a wide range of pH conditions and this approach can be extended to other biosorbent materials using other heavy metals.